Professor bilíngue para surdos: análise da prática de letramento por meio da autoconfrontação - Barroso, Adriana Fernandes (Universidade Federal de São Carlos, 2018)
This study had as main goal to verify the analysis of teachers’ practices, within a classroom interection approach at elementary school. Also, to investigate how the teachers’ self-image, commenting and binding meanings to dialogues and stimulating verbal and social interaction connected with knowledge production. It is a qualitative study, whereby the data were colected in portuguese classes in a elementaly school’ bilingual classrom, in a municipal school located in a city of São Paulo state. The data colect was conducted, first, in the portuguese classes thru shooting the classes in such, the recordings were used in the next stage of the research, when the data was confronted between the teachers and their own work activities, those moments also were recorded and transcribed to analysis, considering the formulation of simple self-confrontation. The data analised, under Vygotsky’ historical social approach, and, with postulates of Bakthin’s theory of enunciation, indicated which are the medication actions that contribute to constructe meanings, considering the relation between writing in portuguese, mediated by discursive interactions in Brazilian Signal Language, showing the methodological effectiveness to create a self-thinking in the teachers that is looking foward to improve their education practices within the classroom. The data analysis indicated that the discussion about educational practices in bilingual classroms is importante, considering the quality of teaching portuguese writing as a second language; furthermore, allow to see aspects of the teacher-learning relationship that will enable possible ways to provide teacher formation for this audience.
Bilingual teacher for deafts: analysis of the practice of lettering by means of self-counseling
Keywords: Educação especial; Surdez; Bilingüismo; Práticas pedagógicas; Professores - Formação; Special education; Deaf; Bilingualism; Education practices; Teachers, Training of; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO